Abschlußbericht über die wissenschaftlichen Ergebnisse der Untersuchung von Silexartefakten der späten Steinzeit aus dem Sultanat Oman - Uerpmann, Margarethe (Institut für Urgeschichte, 1988)
Keywords: Archéologie – Oman

Pre-islamic archaeology of Kuwait, Northeastern Arabia, Bahrain, Qatar, United Arab Emirates and Oman: a bibliography - Haerinck, Ernie; Stevens, Karel Guy (1985)
Keywords: Archéologie – Oman; Bibliographie – Oman

مدينة من الألف الثالث قبل الميلاد في عمان - Frifelt, Karen (وزارة التراث القومي والثقافة, 1983)
Keywords: Archéologie – Oman

ملاحظات حول توزيع الموارد الطبيعية واستثمارها في عمان القديمة - Tosi, Maurizio (وزارة التراث القومي والثقافة, 1983)
Keywords: Archéologie – Oman

La céramique chinoise de Qalʽat al Ṣuḥâr - Pirazzoli-t'Serstevens, Michèle (Arts Asiatiques, 1988)
The Chinese ceramics from Qal'at al- Suhâr The site of Qal'at al-Suhâr on the coast of the Sultanate of Oman, has been excavated by the French archaeological team in Bahrain and Oman conducted by Monique Kervran from 1980 to 1982. The fortress was built in the 13th-14th century above a residential quarter of 9th- 1 1 th century Suhâr. The fort was later constantly altered and partly rebuilt right up until the present century. The Chinese material presented here comes from surveys (1980), the excavation of the fort itself, stratigraphie soundings made perpendicular to the outside of the wall. The sherds have been grouped in series and only some pieces, representatives of each series, are illustrated and described in the catalogue. A study of the Chinese ceramics excavated shows that the Chinese sherds are very abundant, varied and of a rather high quality (white and qingbai wares, Yue ware, Changsha, Xicun...) for the period of the second half of the 9th century until the beginning of the 12th century, which corresponds to the most flourishing period of Suhâr, when the port, like Sîrâf, traded with China, India and the Oriental coast of Africa. Very few specimens were found from the 14th century (celadon and qingbai) to the beginning of 17th century (kraakporselein) . The site yielded a huge quantity of coarse export ware, mainly 19th century. The gap (12th- 18th century) noted in the Chinese material could correspond to the decline of Suhâr's international status.
Keywords: Archéologie – Oman

La citadelle de Hawrat Bargha dans le sultanat d'Oman - Kervran, Monique (Arts Asiatiques, 1987)
The fortress of Hawrat Bargha situated approximately twenty kilometers southwest of Sohar, has been considered, in the nineteenth century, as a fortification established by the Persians during the sixth century AD, in order to control the Batina coast of Oman. Although ceramics very much later than this date had been found within the walled area of the fort, the tradition of its pre-islamic date has persisted.
Keywords: Archéologie – Oman

مستوطنة عرجا لتعدين النحاس: تقرير تمهيدي - Costa, Paolo M. (وزارة التراث القومي والثقافة, 1983)
Keywords: Archéologie – Oman

دراسات لمدينة ظفار (البليد) - Costa, Paolo M. (وزارة التراث القومي والثقافة, 1984)
Keywords: Archéologie – Oman

محصلات العينات الأثرية التي عثر عليها على سطح الارضي - عينات سطح الأرض في عمان في عام 1976 - Cardi, Beatrice de (وزارة التراث القومي والثقافة, 1984)
Keywords: Archéologie – Oman

دراسة لآثار عمان - Cardi, Beatrice de; Whitcomb, Donald S. (وزارة التراث القومي والثقافة, 1983)
Keywords: Archéologie – Oman

III mill. Copper in Oman and the Question of Magan = استغلال النحاس في عمان في الألف الثالثة قبل الميلاد - Weisgerber, Gerd (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Archéologie – Oman

Settlement Patterns in Ancient Oman = دراسة تميدية للاستقرار الحضارى القديم في عمان - Costa, Paolo M. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Archéologie – Oman

بحث الميدني في التعدين القديم في سلطنة عمان - Goettler, G.W.; Firth, Wesley N.; Houston, C. (وزارة التراث القومي والثقافة, 1983)
Keywords: Archéologie – Oman

النفايات التي اكتشفت حديثا بالقرب من قريات - Philipps, S.S.; Wilkinson, T.J. (وزارة التراث القومي والثقافة, 1984)
Keywords: Archéologie – Oman

Water Mills of the Batinah Coast of Oman - Wilkinson, T.J. (Proceedings of the Seminar for Arabian Studies, 1980)
Keywords: Archéologie – Oman

Historical interpretation of the territory of Muscat - Costa, Paolo M. (Oman studies: papers on the archaeology and history of Oman, 1989)
Keywords: Archéologie – Oman

Oman studies: papers on the archaeology and history of Oman - Costa, Paolo M.; Tosi, Maurizio (Istituto italiano per il Medio ed Estremo Oriente, 1989)
Keywords: Archéologie – Oman